PENGAWASAN UNIT PELAKSANA TEKNIS DAERAH (UPTD) PARKIR DINAS PERHUBUNGAN TERHADAP PENGELOLAAN FASILITAS PARKIR KOTA PEKANBARU DI KECAMATAN PEKANBARU KOTA TAHUN 2019 - Eka Rahma Santya Arimbi Br. Sbr; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Parking problems have become a public problem in pekanbaru city. Pekanbaru city is the capital of Riau Province, which acts as the center of government,education,industry and trade,thus giving birth to urbanization. Furthermore, the high flow of urbanization and the rapid growth in the standard of living in urban areas has caused Pekanbaru city to always experience an increase in population, resulting in a increase in the quantity and complexity of vehicles. Therefore, in order to reduce the level of parking congestion in the city of Pekanbaru, parking supervision must be carried out on parking facilities which will be supervised by the regional technical implementation unit (UPTD) for Parking at the transportation service of Pekanbaru city.This study aims to describe the supervision of the parking area technical implantation unit of the transportation service towards the manage district, then also to find out the inhibiting factors of not optimal supervision of the parking area technical implementation unit of the transportation service on the management of the Pekanbaru city parking facilities in the district Pekanbaru city in 2019. The location of the research city, first at the transportation service office, the second on several roads in Pekanbaru city sub-district. Furthermore, data collection techniques are carried out by interview anda documentation.The result of this management is that the supervision of the regional technical implementing unit of the transportation service towards the Pekanbaru city parking facility in the Pekanbaru city sub-district as an effort to monitor parking in Pekanbaru city has not been running optimally. This is due to several factors such as the lack of parking supervision personnel at the UPTD, operational resources, and the behavior of users of parking services of and inadequate facilities. Keywords: Supervision, and Management of Parking Facilities